Penerapan Metode User Experience Questionnaire (UEQ) Sebagai Evaluasi User Experience Pada Aplikasi Kita Bestee - Permana, M. Anton; Paisal, Irvan; Lattu, Arny (Universitas Muhammadiyah Riau, 2025)
User experience plays a crucial role in determining the success of a digital application, including the Kita Bestee application used by facilitator companions at PT Bank BTPN Syariah Tbk. This study aims to evaluate the user experience (UX) of the Kita Bestee application using the User Experience Questionnaire (UEQ), which covers six key dimensions: attractiveness, clarity, efficiency, accuracy, stimulation, and novelty. Using a quantitative approach, data were collected through questionnaires distributed to 75 active facilitators in Sukabumi City and Regency. The data were analyzed with the UEQ Data Analysis Tool version 12 and supported by validity and reliability testing using SPSS version 26. The results showed that clarity received the highest score of 0.88, followed by attractiveness (0.76) and stimulation (0.73), while efficiency and novelty scored lower and require improvement. Based on UEQ international benchmarks, most UX dimensions fall into the above average category but have not yet reached the excellent level. Overall, the findings indicate that the Kita Bestee application provides a fairly positive user experience, though enhancements are still needed, especially in terms of innovation and interface efficiency, and the study offers strategic recommendations to support future UX improvements.